2013
DOI: 10.1039/c3cp50767j
|View full text |Cite
|
Sign up to set email alerts
|

High power enzymatic biofuel cell based on naphthoquinone-mediated oxidation of glucose by glucose oxidase in a carbon nanotube 3D matrix

Abstract: We report the design of a novel glucose/O2 biofuel cell (GBFC) integrating carbon nanotube-based 3D bioelectrodes and using naphthoquinone-mediated oxidation of glucose by glucose oxidase and direct oxygen reduction by laccase. The GBFCs exhibit high open circuit voltages of 0.76 V, high current densities of 4.47 mA cm(-2), and maximum power output of 1.54 mW cm(-2), 1.92 mW mL(-1) and 2.67 mW g(-1). The GBFC is able to constantly deliver 0.56 mW h cm(-2) under discharge at 0.5 V, showing among the best in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
138
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(146 citation statements)
references
References 16 publications
7
138
1
Order By: Relevance
“…Most of these substrates, such as sugars and linear alcohols (glucose, maltose, lactose, ethanol, methanol and fructose), are considered as alternative fuels with high energy densities. [1][2][3][4][5][6][7][8] During recent decades, an exhaustive list of EFCs can be found in the literature aiming to exploit these alternative sources or to develop self-powered electrochemical biosensors working in vitro or in vivo. 6 In EFCs, the fuels undergo bioelectrocatalytic oxidation at the anode operating commonly with flavin adenine dinucleotide-dependent (FAD) oxidases and dehydrogenases as well as nicotinamide adenine dinucleotidedependent (NAD) dehydrogenases.…”
mentioning
confidence: 99%
“…Most of these substrates, such as sugars and linear alcohols (glucose, maltose, lactose, ethanol, methanol and fructose), are considered as alternative fuels with high energy densities. [1][2][3][4][5][6][7][8] During recent decades, an exhaustive list of EFCs can be found in the literature aiming to exploit these alternative sources or to develop self-powered electrochemical biosensors working in vitro or in vivo. 6 In EFCs, the fuels undergo bioelectrocatalytic oxidation at the anode operating commonly with flavin adenine dinucleotide-dependent (FAD) oxidases and dehydrogenases as well as nicotinamide adenine dinucleotidedependent (NAD) dehydrogenases.…”
mentioning
confidence: 99%
“…[26][27][28] Since the current challenges for biofuel cell development lie in deeper oxidation and improved energy density, 29 recent reports have been mainly focused on disaccharides or polysaccharide based biofuel cells. 30,31 Hickey et al 32 reported an enzyme cascade system employing invertase, fructose dehydrogenase and glucose oxidase immobilized in ferrocene-modified linear poly(ethyleneimine) (Fc-C 6 -LPEI) hydrogel, which was then drop casted onto carbon electrode for catalyzing sucrose oxidation in a biofuel cell.…”
mentioning
confidence: 99%
“…Currently, high performance glucose biofuel cells mostly employ Carbon Nanotubes (CNTs) as the electrode materials due to their high surface area mediated electron transfer. The development of these nanostructured electrode materials have been show to greatly improve the electroactive area for enzyme immobilization [18,65,66]. Several reports also demonstrated the transition from in vitro to in vivo characterization of enzymatic glucose biofuel cells [13,15,24,25,67,68].…”
Section: In Vivo Implantations Of Enzymatic Biofuel Cellmentioning
confidence: 99%